Usinagem do aço inoxidável austenítico ABNT 316 UF com aplicação de fluido de corte a alta pressão - Naves, Vitor Tomaz Guimarães (2013)
The use of cutting fluid during the cutting process, when chosen and applied properly, reduce the heat generated during the chip formation as well as reducing the friction between the chip and the tool thus may increase the tool life, improve the finish surface and decrease tool wear rate. Cutting fluids may also help in reducing cutting forces and contribute to a lower power consumption by the machine tool during the manufacturing processes. Cutting fluids work as a lubricant to reduce the contact area between chip and tool, and their efficiency depends on the ability to penetrate the chip-tool interface and to create a thin layer in the shortest available time. High-pressure jet-assisted machining has become a powerful technique to help the cutting fluid to attain regions very close to the cutting edge and increase production efficiency. The main advantages of this technique are improved chip control, increased tool life, lower cutting temperature and better surface integrity. The objective of this work is to investigate the action of the cutting fluid at high pressure during the machining process of austenitic stainless steel ABNT 316 UF. The experiments were carried out in a turning operation and the cutting fluid was applied at different pressures (10, 15 and 20 MPa) between the chip and tool at the rake face The respective flow rates of these conditions are pressures of 13.2 l / min and 16.8 l / min and 18.6 l / min. The results were compared to dry cutting and wet cutting. Cemented carbide tools of class ISO K coated with TiN, Al2O3 and Ti (C,N), using the chemical vapor deposition at medium temperature technique (MTCVD), were employed. The cutting fluid used was a vegetable oil with concentration of 5% and 10%. The trials were performed in a numerically controlled lathe with 11 kW main engine power and speed range 3-3000 rpm. The cutting parameters were: cutting speed 300 m/min, feed 0.2 mm/rev and depth of cut of 1 mm. The signals monitored were: electrical power consumed by the machine, the components of the cutting forces, measuring of surface roughness, chip formation, chip micro hardness , wear mode and wear mechanism of cutting tools. The results showed that the use of cutting fluid at high pressure increased the tool life. Roughness surface, cutting forces and power machining shown reduced when the cutting fluid were applied under high pressure. Analysis by scanning electron microscopy and electron backscattering showed that the area and the length of chiptool contact was significantly reduced when the cutting fluid was applied at high pressure. The main wear mechanism observed on the rake face and the flank face was adhesion. The highpressure coolant technique was more efficient than both overhead fluid applications and dry cutting with regard to the reduction of cutting tool wear. The lowest wear was obtained when the fluid was applied with a concentration of 10% and at a pressure of 10 MPa. The high pressure jet coolant shown to be an efficient chip breaker, producing chip fragmented.